TEKNOLOGI INFORMASI DAN REPOSISI FUNGSI MANAJEMEN SUMBER DAYA MANUSIA - Anton Agus Setyawan; Rini Kuswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2006)
The development of information technology has major influence to the role of human resourcemanagement (HRM) in a company. HRM transforms from administrative function to become strategicfunction. HRM practice has develop itself into four major roles, they are: strategic partner,administrative expert, employee champion and agent of change. Several new issues has emerges as aresult of HRM transformation, they are: knowledge base organization, strategic HRM and knowledgemanagement. This paper tries to give theoritical explanation about those issues. The goal of this paperis to encourage research about the new role of HRM in business practice.